Perceraian dengan Khulu’ dalam Perspektif Peraturan Perundang-undangan yang Berlaku di Indonesia - Wianda, Alvi; Amin Qodri, Muhammad; Syelvita, Rema (Universitas Jambi, Fakultas Hukum, 2026)
The purpose of this study is to determine and analyze: 1) the legal regulation of khulu' in the perspective of the applicable laws and regulations in Indonesia, and 2) the urgency of the regulation of khulu' explicitly stated in the National legal system in Indonesia. The type of research is normative juridical. The results of the study indicate that the legal regulation of khulu' in the perspective of the applicable laws and regulations in Indonesia refers to Article 116, Article 148 and Article 161 of the Compilation of Islamic Law, while in Indonesian Civil Law there is no regulation regarding khulu', either in the Civil Code, the Marriage Law or in Government Regulations. The urgency of regulating khulu' is explicitly stated in the National legal system in Indonesia to clarify and provide legal force for the implementation of khulu', to help wives who have difficulty divorcing their husbands, to provide a balance of rights between husband and wife, to be a means to protect the wife's rights from unfair or inhumane treatment from her husband, and to minimize conflict between husband and wife because the wife has a clear way out if the marriage does not go well.